Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea) - Kashani, Ghasem M. (Zootaxa, 2019)
The terrestrial isopod species of the subgenus Hemilepistus (Desertellio) are revised. Hemilepistus ruderalis (Pallas, 1771), H. heptneri Borutzky, 1954, H. pavlovskii Borutzky, 1954 and H. fedtschenkoi (Uljanin, 1875) are redescribed and their diagnostic characters are figured. Three species namely H. nodosus Budde-Lund, 1885, H. zachvatkini Verhoeff, 1930 and H. buddelundi Borutzky, 1945 are synonymized with H. fedtschenkoi, and H. russonovae Borutzky, 1945 is considered as a synonym of H. ruderalis. An identification key to Desertellio species is provided.